"I" vs "me": the urbanization of "post-80s" and "post-90s" Chinese migrant workers. Issue 1 (13th February 2023) - Xu, Siyu; He, Jun; Aziz, Noshaba
Abstract: The difference in self-identity among migrant workers of the new generation leads them towards different desires regarding urbanization. In this regard, it is imperative to explore the influence of self-identity on the migrant workers' willingness to stay. To explore the phenomenon empirically, the current study used data sourced from the China Migrants Dynamics Survey (CMDS), during the year, 2017. The study employed the Heckman two-stage selection model to explore the study objective. Further, the study also employed the machine learning methods for robustness check. The outcome showed that the "I" identity has a more significant impact on the urbanization by migrant workers belonging to the "post-90s". In comparison, the identity of "Me" has a more significant impact on the urbanization by migrant workers belonging to the era of the 1980s. And it is clear that if "post-80s" and "post-90s" migrant workers are uniformly divided into the union of new generation, the differences and characteristics within them may conceal. The overall findings proposes that based on the differences in migrant workers' self-identity, both born in the 1980s and 1990s, there is a need to formulate related policies to promote their residence and boost urbanization.